2015
DOI: 10.3390/molecules200712959
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Stability and Antioxidant Activity of Spirodiazaselenuranes

Abstract: Spirodiazaselenuranes are structurally interesting compounds and the stability of these compounds depends highly on the nature of the substituents attached to the nitrogen atoms. Aromatic substituents are known to play important roles in stabilizing the Se-N bonds in spiro compounds. In this study, several spirodiazaselenuranes are synthesized by introducing benzylic and aliphatic substituents to understand their effect on the stability of the Se-N bonds and the antioxidant activity. Replacement of phenyl subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…[61] N-Benzylic, N-alkyl and N-heteroaryl derivatives, as well as their selenide precursors, were less activet han ebselen, which provided V 0 = 98.0 mm min À1 in the coupled reductase assay with hydrogen peroxidei napH 7.5 phosphate buffer. [62] As lightly different mechanism from that shown in Scheme 8 was proposed for the dioxyspiro derivatives at high thiol concentrations,w herein direct reduction of the selenoxide intermediate by the thiol is possible, withoutr egeneration of the spirodiaza compound. Both the spirodiazaselenuranes and their precursor selenides were also reported to inhibit peroxynitrite-mediated nitration of bovine serum albumina nd oxidation of dihydrorhodaminet or hodamine.…”
Section: Spirodiazaselenuranesmentioning
confidence: 97%
See 2 more Smart Citations
“…[61] N-Benzylic, N-alkyl and N-heteroaryl derivatives, as well as their selenide precursors, were less activet han ebselen, which provided V 0 = 98.0 mm min À1 in the coupled reductase assay with hydrogen peroxidei napH 7.5 phosphate buffer. [62] As lightly different mechanism from that shown in Scheme 8 was proposed for the dioxyspiro derivatives at high thiol concentrations,w herein direct reduction of the selenoxide intermediate by the thiol is possible, withoutr egeneration of the spirodiaza compound. Both the spirodiazaselenuranes and their precursor selenides were also reported to inhibit peroxynitrite-mediated nitration of bovine serum albumina nd oxidation of dihydrorhodaminet or hodamine.…”
Section: Spirodiazaselenuranesmentioning
confidence: 97%
“…Substituent effects were quite different from those observed with spirodioxyselenuranes, and optimum reactivity in both the spirodiazaselenuranes and their precursor selenides was obtained with m ‐OH and p ‐CO 2 H substituents, while o ‐OMe and p ‐Me groups suppressed the reaction the most (Table ) . N‐Benzylic, N‐alkyl and N‐heteroaryl derivatives, as well as their selenide precursors, were less active than ebselen, which provided V 0 =98.0 μ m min −1 in the coupled reductase assay with hydrogen peroxide in a pH 7.5 phosphate buffer . A slightly different mechanism from that shown in Scheme was proposed for the dioxyspiro derivatives at high thiol concentrations, wherein direct reduction of the selenoxide intermediate by the thiol is possible, without regeneration of the spirodiaza compound.…”
Section: Spirodiazaselenuranesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, ebselen is not water soluble, making rapid intravenous administration impossible, and has shown cellular toxicity in some studies . Other selenium‐containing GPX mimics have been synthesized, and some have potent GPX‐like activity including cyclic seleninate and selenenate esters, spirodioxyselenuranes, pincer selenuranes, and spirodiazaselenuranes . However, many of these compounds are expected to be toxic, are not water soluble, are unstable, or quickly lose catalytic activity in the presence of thiols …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Other selenium-containing GPX mimics have been synthesized, and some have potent GPX-like activity including cyclic seleninate and selenenate esters, [16][17][18][19][20][21] spirodioxyselenuranes, [22][23][24] pincer selenuranes, 22 and spirodiazaselenuranes. 25,26 However, many of these compounds are expected to be toxic, are not water soluble, are unstable, or quickly lose catalytic activity in the presence of thiols. 3 One possible reason that GPX cannot respond optimally to very high concentrations of H 2 O 2 , as occurs during reperfusion injury, is that it has been shown that GPX can be inactivated by conversion of the Sec residue to dehydroalanine (DHA).…”
mentioning
confidence: 99%